a) Find f_{xy}(x,y); ((4x^{2})/y) + ((y^{2})/(2x)). b) Find f_{xy}(x,y); ln(x^{2} - y^{2}). c)...


a) Find {eq}f_{xy}(x,y); \, \frac{4x^{2}}{y} + \frac{y^{2}}{2x}. {/eq}

b) Find {eq}f_{xy}(x,y); \, \ln(x^{2} - y^{2}). {/eq}

c) Find {eq}\frac{dw}{dt} {/eq} using the chain rule.

{eq}w = \ln(xy) + xy^2; \, x = e^{t}; \, y = e^{-t} {/eq}

Chain Rule:

Suppose {eq}x=x\left( t \right) {/eq} and {eq}y=y\left( t \right) {/eq} and {eq}w=f\left( x,y \right) {/eq}, then

{eq}\frac{dw}{dt}=\frac{dw}{dx}.\frac{dx}{dt}+\frac{dw}{dy}.\frac{dy}{dt} {/eq}

Similarly, if we have any function of three or more variables, we can find the derivative using chain rule.

Partial derivatives of a multi-variable function are calculated the same way as we differentiate a single variable function. We hold all variables except one constant.

Answer and Explanation: 1

Part (a):

{eq}\begin{align} & f\left( x,y \right)=\frac{4{{x}^{2}}}{y}+\frac{{{y}^{2}}}{2x} \\ & f\left( x,y \right) =\frac{4{{x}^{2}}}{y}+\frac{{{y}^{2}}}{2}{{x}^{-1}} \\ \end{align} {/eq}

Take partial derivative w.r.t. {eq}x {/eq}. Use power rule of differentiation

{eq}\begin{align} & {{f}_{x}}\left( x,y \right)=\frac{8x}{y}-\frac{{{y}^{2}}}{2}{{x}^{-2}} \\ & {{f}_{x}}\left( x,y \right) =\frac{8x}{y}-\frac{{{y}^{2}}}{2{{x}^{2}}} \\ \end{align} {/eq}

Now do partial differentiation w.r.t. {eq}y {/eq}

{eq}\begin{align} & {{f}_{x}}\left( x,y \right)=8x{{y}^{-1}}-\frac{{{y}^{2}}}{2{{x}^{2}}} \\ & {{f}_{xy}}\left( x,y \right)=-8x{{y}^{-2}}-\frac{2y}{2{{x}^{1}}} \\ & {{f}_{xy}}\left( x,y \right) =\boxed{\frac{-8x}{{{y}^{2}}}-\frac{y}{{{x}^{2}}}} \\ \end{align} {/eq}

{eq}\; {/eq}

Part (b):

{eq}f\left( x,y \right)=\ln \left( {{x}^{2}}-{{y}^{2}} \right) {/eq}

Take partial derivative w.r.t. {eq}x {/eq}. Use chain rule {eq}\left( \frac{d}{dx}f\left( g\left( x \right) \right)=f'\left( g\left( x \right) \right)g'\left( x \right) \right) {/eq} and {eq}\frac{d}{dx}\left[ \ln \left( x \right) \right]=\frac{1}{x} {/eq}

{eq}\begin{align} & {{f}_{x}}\left( x,y \right)=\frac{\partial }{\partial x}\left( \ln \left( {{x}^{2}}-{{y}^{2}} \right) \right) \\ & {{f}_{x}}\left( x,y \right) =\left( \frac{1}{{{x}^{2}}-{{y}^{2}}} \right).\frac{\partial }{\partial x}\left( {{x}^{2}}-{{y}^{2}} \right) \\ & {{f}_{x}}\left( x,y \right) =\frac{2x}{{{x}^{2}}-{{y}^{2}}} \\ \end{align} {/eq}

Now take partial derivative w.r.t. {eq}y {/eq}. Use power rule and chain rule

{eq}\begin{align} & {{f}_{x}}\left( x,y \right)=2x{{\left( {{x}^{2}}-{{y}^{2}} \right)}^{-1}} \\ & {{f}_{xy}}\left( x,y \right)=-2x{{\left( {{x}^{2}}-{{y}^{2}} \right)}^{-2}}.\frac{\partial }{\partial y}\left( {{x}^{2}}-{{y}^{2}} \right) \\ & {{f}_{xy}}\left( x,y \right)=\frac{\left( -2x \right)\left( -2y \right)}{{{\left( {{x}^{2}}-{{y}^{2}} \right)}^{2}}} \\ & {{f}_{xy}}\left( x,y \right)=\boxed{\frac{4xy}{{{\left( {{x}^{2}}-{{y}^{2}} \right)}^{2}}}} \\ \end{align} {/eq}

{eq}\; {/eq}

Part (c):

{eq}\begin{align} & w=\ln \left( xy \right)+x{{y}^{2}} \\ & x={{e}^{t}} \\ & y={{e}^{-t}} \\ \end{align} {/eq}

Using chain rule for two variable function

{eq}\begin{align} & \frac{dw}{dt}=\frac{dw}{dx}.\frac{dx}{dt}+\frac{dw}{dy}.\frac{dy}{dt} \\ & \frac{dw}{dt}=\frac{d}{dx}\left[ \ln \left( xy \right)+x{{y}^{2}} \right].\frac{d}{dt}\left( {{e}^{t}} \right)+\frac{d}{dy}\left[ \ln \left( xy \right)+x{{y}^{2}} \right].\frac{d}{dt}\left( {{e}^{-t}} \right) \\ \end{align} {/eq}

Again use the rule {eq}\frac{d}{dx}f\left( g\left( x \right) \right)=f'\left( g\left( x \right) \right).g'\left( x \right) {/eq}

{eq}\begin{align} & \frac{dw}{dt}=\left[ \frac{1}{xy}.\frac{d}{dx}\left( xy \right)+{{y}^{2}} \right]{{e}^{t}}+\left[ \frac{1}{xy}\frac{d}{dy}\left( xy \right)+2xy \right]\left( -{{e}^{-t}} \right) \\ &\frac{dw}{dt}=\left( \frac{1}{xy}.y+{{y}^{2}} \right){{e}^{t}}+\left( \frac{1}{xy}x+2xy \right)\left( -{{e}^{-t}} \right) \\ & \frac{dw}{dt}=\boxed{\left( \frac{1}{x}+{{y}^{2}} \right){{e}^{t}}-\left( \frac{1}{y}+2xy \right){{e}^{-t}}} \\ \end{align} {/eq}

Learn more about this topic:

The Chain Rule for Partial Derivatives


Chapter 14 / Lesson 4

This lesson defines the chain rule. It goes on to explore the chain rule with partial derivatives and integrals of partial derivatives.

Related to this Question

Explore our homework questions and answers library